The Indicators of Creative Thinking Patters in Architectural Design and The Forms of Continuity for The Designer's Direction of its - Suha Haddan ALdahwia; Jassim Mahammed Neama (Iraqi Journal of Architecture and Planning, 2018)
There is no doubt that creative thinking an area refined human activity since ancient times, for that scientific research institutions attented it since the mid-twentieth century , society humanitarian civilized increasingly need more to the creative which can not be achieved without the development of skills and thinking abilities activity creative different cultural norms . Despite the issue of architectural creativity, especially in the architectural design process importance, but can say that and also that every thinking in any area of life areas of special rules and attributes define features pattern, the to think of the architectural work to him is the other his patterns have rules and attributes define features creative. What research aims to create a clear vision for patterns of creative thinking in the field of architecture] that can be used as a yardstick to judge the availability of creative thinking patterns in architectural work indicators, and determine the forms of communication between the architect and these patterns, so the search is divided into five parts; the first part deals synopsis of thinking and patterns, while Part II deals with extraction and research of the problem and research objectives and approach. The third part presents the study that have been developed in two dimensions; creative thinking in architectural design and stages, and creative thinking skills in architectural design. In the fourth part is the discussion of creative thinking patterns and indicators. general conclusions and recommendations made at the fifth and final